Overview of Antibiotic Prescribing Based on Aware Category at Fatmawati Hospital in the Period of May 2024 - November 2024 - N, Panggabean Sylvia; Retnosari, Retnosari; Subhan, Subhan; Latuperissa, Debby (Eduvest - Journal of Universal Studies, 2025)
WHO issued AWaRe guidelines to optimize the use of antibiotics to prevent resistance. This guideline is also used in Indonesia, including hospitals. Fatmawati is one of the government hospitals in DKI Jakarta that has the most patient visits. To describe the prescribing of antibiotics in hospitals. Fatmawati based on the AwaRe category. The design of this study uses a qualitative description with a total sampling method and then analyzed using Microsoft Excel. The most prescribing of antibiotics at Fatmawati Hospital as many as 86,833 were in the watch (61.5%), access (30.7%) and last reserve (7.8%) categories. The most prescribed antibiotics in the access group are metronidazole (25.655%), ampicillin (20.835%), gentamicin (12.273%) with the most prescribed dosage forms being tablets (35.064%), sterile powder (30.123%), infusion (22.154%). In the watch group, the most prescribed are ceftriaxone (26.887%), cefixime (22.363%), levoflosacin (17.492%) with the most prescribed dosage forms being sterile powder (47.992%), capsules (21.463%), infusions (14.232%). In the reserve group, the most prescribed are meropenem (62.405%), cefepime (8.705%), ampiscillin/sulbactam (7.919%) with the most prescribed dosage forms being sterile powder (90.93%), tablets (5.695%), and infusions (4.197%). The results showed that the most antibiotic prescriptions were in the watch group compared to the access category. These findings show that it is necessary to re-evaluate PPAB at the hospital. Fatmawati